A new many-body potential with the second-moment approximation of tight-binding scheme for Hafnium - Lin, DeYe; Wang, Yi; Shang, ShunLi; Lu, ZhaoPing; Liu, ZiKui; Hui, XiDong (Science China. Physics, mechanics & astronomy, 2013)
In this work, we develop a new many-body potential for alpha-hafnium（α-Hf） based on the second moment approximation of tight-binding（TB-SMA） theory by introducing an additional Heaviside step function into the potential model and a new analytical scheme of density function. All the parameters of the new potential have been systematically evaluated by fitting to ground-state properties including cohesive energy, lattice constants, elastic constants, vacancy formation energy, structure stability and equation of state. By using the present model, the melting point, melt heat, thermal expansion coefficient, point defects, and low-index surface energies of α-Hf were calculated through molecular dynamics simulations. Comparing with experiment observations from others, it is shown that these properties can be reproduced reasonably by the present model, some results being more consistent to the experimental data than those by previous suggested models. This indicates that this work is sutiable in TB-SMA potential for hexagonal close packed metals.